Localizing Islam in the West - Ahmed Ali Salem (International Institute of Islamic Thought, 2016)
Ali Mazrui attempted to correct many misunderstandings of Islam in the West and demonstrate its closeness to and impact upon western civilization in several ways. For example, Islam is a fellow monotheistic religion, has preserved and added to the Greco-Roman legacy, preceded mercantilism and capitalism in hailing free trade and hard work, and modeled the western view of a tripartite world in the second half of the twentieth century. Mazrui's interest in studying Islam was originally part of his general exploration of postcolonial Africa. Although trained in mainstream political science, which emphasizes materialism, he quickly realized that culture is a powerful key to understanding politics. From this cultural optic, Mazrui began to interpretatively revive Islam as a powerful factor in African politics and highlight its values as capable of improving African conditions. His most celebrated work, namely, the 1986 television series "Africa: The Triple Heritage," was in part a call to reconsider Islam as a major foundation of African societies. His cultural studies helped him gain new constituencies among the larger Muslim community and then go global. His global studies upheld Islam against both Marxism and racism, which helped him escape the narrowness of Afro-centrism and broaden his concept of pan-Africanism to include not only sub-Saharan Africans and their Arab neighbors to the north, but also the Arab neighbors to the east and diasporic Africans as well. In this paper, I use many of Mazrui's publications that discuss various Islamic issues in Africa, the West, and globally.